Exploring EFL Teachers’ Knowledge on the Utilization of Platform Merdeka Mengajar (PMM): Challenges, Possibilities and Practices - Anggra Hermawan, Hengki; Wirza, Yanty (ETERNAL (English Teaching Journal), 2025)
In supporting the implementation of The Emancipated Curriculum, Merdeka Mengajar is the main tool that the government use to spread information and help the implementation of The Emancipated Curriculum. In The Pangandaran district, the Emancipated Curriculum has been 100% implemented in formal education. In implementing The Emancipated Curriculum, there are many challenges that teachers face; they need a comprehensive understanding of the Emancipated Curriculum to implement the curriculum. This study aims to give an overview of how the utilization of PMM to support Pangandaran EFL teachers’ knowledge in implementing Emancipated Curriculum and the challenges, possibilities, and Practices in the utilization of PMM are based on EFL Pangandaran Teachers’ perspective. This study used qualitative methods with using documentation, questionnaires, and interviews to collect the data. Documentations were made by extracting data from the West Java Province BBMP website. The questionnaire involved 50 EFL teachers in The Pangandaran district. Interviews were conducted with two EFL teachers in The Pangandaran district. The result shows that the use of Platform Merdeka Mengajar (PMM) in The Pangandaran district has a score of 41.1% good, 50% quite good, and 8.9% need to be improved. 100% of the samples have installed the PMM application on their devices and have started studying the material and features of the application. Most EFL Teachers still face challenges in the utilization of PMM and the implementation of The Emancipated Curriculum itself.